Звуковий сигналізатор розумного будинку - Степанов, І. В. (ХНУРЕ, 2020)
When designing a smart home, there is a need to develop all kinds of alarms. This work is devoted to the development of a sound signaling device that can work in the home security system, in the power supply system and others. Since the device must operate continuously regardless of the location of operation, whether it is a living space, basement or office space, both from stationary power and stand-alone. Power protection is required to prevent фincorrect voltage polarity.
Keywords: розумний дім; сигналізатор; Atmega; мікроконтролер